Bronchial hyperreactivity to leucotriene D4 and histamine in exogenous asthma. Issue 6480 (18th May 1985) - Bisgaard, H; Groth, S; Madsen, F
Abstract : Reactivity of the small and large airways to inhaled leucotriene D4, one of the leucotrienes that constitute slow reacting substance of anaphylaxis, was studied in eight patients with exogenous asthma and nine healthy subjects with no history of atopy. Non-cumulative dose response relations were constructed for leucotriene D4 in a randomised, double blind set up. Reactivity to the leucotriene was compared with reactivity to histamine in the two groups. Both groups reacted to leucotriene D4 with significant airway obstruction evident in forced expiratory volume in one second (FEV1), peak expiratory flow rate, maximal expiratory flow rate at 30% of forced vital capacity estimated from a partial flow volume curve initiated at 50% of vital capacity (V30), and an increase in volume of trapped gas. The airways of the patients were significantly (p less than 0.01) more reactive to leucotriene D4 than those of the controls. The differences were in order of magnitude, 10(2)-10(3) for FEV1 but only about 15 for V30 (p less than 0.05). The hyperreactivity of the airways of the asthmatic subjects to leucotriene D4 was comparable to that to histamine. Inhalation of leucotriene D4 caused pronounced dyspnoea only among the patients. The findings suggest a role for leucotriene D4 in human bronchial asthma.